Two-Phase Mixture Numerical Study of Nanofluid Flow in a Lithium-Ion Battery Cooling System - Benabderrahmane, Amina; Laouedj, Samir (Ingeniería, 2025)
Context: The cooling performance of a thermal battery plays a critical role in its efficiency, lifespan, and safety. This importance stems from the heat generated during charging and discharging processes. As temperatures rise, key battery characteristics are significantly affected. Method: Using the ANSYS Fluent computational fluid dynamics software, a 2D numerical simulation was conducted to study the cooling of a lithium-ion battery in the presence of nanofluids. The flow of nanofluids was analyzed using the multiphase mixture model. Results: It was found that the coolant inlet velocity significantly impacts the module's temperature distribution and the maximum temperature difference, where the temperature differences almost stabilize for inlet velocities exceeding 0.3 m/s. The effect of using nanofluids was studied with three different types of nanoparticles (alumina, copper, and fullerene) dispersed in water as the base fluid. The results show that the temperature difference in the module varies depending on the nature and volume fraction of the nanoparticles. The incorporation of nanofluids leads to a significant reduction in module temperatures. Fullerene nanoparticles were found to exhibit superior cooling performance compared to other nanoparticle types. On the other hand, a nanoparticle volume fraction exceeding 2% yields a nearly uniform temperature distribution within the module, as well as reduced cell temperatures. Conclusions: Nanofluids have an important effect on battery cooling. Optimizing nanoparticle concentration and flow dynamics can effectively improve thermal management strategies for lithium-ion battery systems.